2013
DOI: 10.1186/1750-1172-8-61
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of therapy uncertainties in Dystrophic Epidermolysis Bullosa: where should research direct to? an example of priority setting partnership in very rare disorders

Abstract: BackgroundDystrophic Epidermolysis Bullosa (DEB) is a rare genodermatosis (7 cases per million) that causes blisters and erosions with minor trauma in skin and mucosa, and other systemic complications. A recently updated systematic review showed that the research evidence about DEB therapies is poor. As new trials in DEB are difficult and expensive, it is important to prioritizise research that patients and clinicians consider more relevant.ObjectivesTo describe and prioritize the most important uncertainties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Priority setting methods have been established and used by almost 30 JLA PSPs, including prostate cancer [19], vitiligo [20], palliative and end of life care [21], childhood neurodisability [22], and dystrophic epidermolysis bullosa [23]. Details of the methods agreed and adopted can be found in a number of publications [24][25][26][27][28], and therefore only a brief summary is presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Priority setting methods have been established and used by almost 30 JLA PSPs, including prostate cancer [19], vitiligo [20], palliative and end of life care [21], childhood neurodisability [22], and dystrophic epidermolysis bullosa [23]. Details of the methods agreed and adopted can be found in a number of publications [24][25][26][27][28], and therefore only a brief summary is presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Previous priority-setting partnerships following the James Lind Alliance approach conducted preliminary surveys and voting exercises to identify and prioritize treatment uncertainties, removed questions that had been addressed by existing evidence, and conducted a face-to-face workshop to prioritize the remaining questions. 20,24,33,34 However, we chose to omit these initial steps to ascertain whether patients/caregivers and health professionals could identify research questions and priorities together from the outset. We have shown that it is possible to compress the research priority-setting partnership process, which has implications for cost, resources, and feasibility.…”
Section: Strengths and Potential Limitationsmentioning
confidence: 99%
“…Three papers contained examples of patient input in priority-setting for research [77][78][79]. Two described multistakeholder processes that engaged representatives from patient organizations, physicians, other healthcare professionals, basic scientists and researchers in health economics and health policy.…”
Section: Setting Research Prioritiesmentioning
confidence: 99%
“…Two described multistakeholder processes that engaged representatives from patient organizations, physicians, other healthcare professionals, basic scientists and researchers in health economics and health policy. Through surveys, workshops, and Delphi processes, lists of priority rare diseases or treatment-related uncertainties to be addressed through future research were constructed [78,79]. The third example outlined an approach used to incorporate patient priorities into a national research agenda for neuromuscular diseases in The Netherlands [77].…”
Section: Setting Research Prioritiesmentioning
confidence: 99%